Research on the Performance and Energy Saving of Solar-Coupled Air Source Heat Pump Heating System: A Case Study of College Dormitory in Hot Summer and Cold Winter Zone - Xu Wang; Shidong Wang; Tao Li (Energies, 2025)
As a densely populated area, college student dormitories consume a large amount of electricity every year to heat the domestic hot water used by students. Applying solar energy to hot water systems can effectively alleviate this situation. This paper first conducts a simulation of the hot water load and the calculation of the available area of the solar roof in a dormitory building of a certain university. Then, different solar-coupled air source heat pump systems were designed, and simulation models of the two systems were established. The thermal performance parameters and solar energy utilization of the two systems were discussed, and the energy efficiency, economy, and environmental protection of the two systems were analyzed. The results show that after coupling with the solar collector, the system operation time is shortened by 26.2%, the annual performance coefficient is 3.4, which is 0.8 higher than that of the original system, and the annual heating energy consumption is reduced by 24.4%. In contrast, the annual energy self-sufficiency rate of the photovoltaic coupled with air source heat pump system is 94.6%, achieving nearly zero energy consumption for heating.